The representation of the European Union in the Spanish media: dominant themes and actors on the Europeanization process - García-Carretero, Lucía; Establés, María-Josefa; Pérez-Escoda, Ana; Boulos, Sonia (Estudios sobre el Mensaje Periodístico, 2022)
The global events of the last two years have created an intense reality from an informative, institutional, and political perspectives. The media have enhanced their legitimacy in the face of the infodemia caused by Covid-19 and the Ukrainian War, establishing a specific agenda-setting on the configuration of the European Union. In this context, the research presented aims to analyze the mediatization of discourses on the EU in the Spanish media. Using a qualitative content analysis methodology, a sample of 543 news items published and/or broadcast in six Spanish media (El País, El Confidencial, ABC, El Diario.es, TVE and Antena 3) were analyzed over a period of nine months. The coding and analysis of the sources studied resulted in the detection of the most prominent topics and actors in the media discourse on Europeanisation issue.
Keywords: European Union; Media; Europeanization; News; Content analysis